Bacteria Isolations from Broiler and Layer Chicks in Zambia. (3rd September 2012) - Munang'andu, Hetron Mweemba; Kabilika, Swithine Hameenda; Chibomba, Oliver; Munyeme, Musso; Muuka, Geoffrey Munkombwe
Abstract : Chick mortality (CM) is one of the major constraints to the expansion of the poultry industry in Zambia. Of the 2, 829 avian disease cases submitted to the national diagnostic laboratory based at the Central Veterinary Research Institute in Lusaka between 1995 and 2007, 34.39% (973/2, 829) were from CM cases. The disease accounted for 40.2% (218, 787/544, 903) mortality in the affected flocks with 89.6% (196, 112/218, 787) of the affected birds dying within seven days. Major bacteria species involved were Escherichia coli, Salmonella gallinarum, and Proteus species being isolated from 84.58%, 46.15%, and 26.93% of the reported CM cases (n = 973 ), respectively. Detection of Salmonella typhimurium, Salmonella enteritidis, and Salmonella dublin indicates that poultry has the potential of transmitting zoonotic pathogenic bacteria to humans. The proportion of Salmonella gallinarum reactors in the adult breeding stock was generally low (<0.5%) throughout the study period although its prevalence in CM cases was correlated (r = 0.68, P < 0.011 ) with seroprevalence of the same pathogen in the adult breeding stock. Given that the disease accounts for a large proportion of the avian diseases in Zambia as shown in the present study (34.39%, n = 2, 829), it is imperative that an effective disease control strategy aimed at reducing its occurrence should be developed.